2022
DOI: 10.3389/fmats.2022.958472
|View full text |Cite
|
Sign up to set email alerts
|

Modeling precipitation kinetics in multicomponent alloys during deformation

Abstract: A new mean-field modeling tool is developed to correctly tackle the problem of precipitation during deformation. The model is an extension of a previously developed Langer–Schwartz–Kampmann–Wagner precipitation modeling approach for multicomponent alloys. The latter is now integrated together with Thermo-Calc software and with physically based equations describing the evolution of the dislocation density during hot-working. New equations for the nucleation barrier and the critical size have also been added to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…This phenomenon was evident due to the evolution of the material properties, namely, the concurrent increase in electrical conductivity and hardness. Furthermore, several previous investigations have shown that a high dislocation density significantly improves the kinetics of precipitation [5,[34][35][36] and recrystallization [33,37,38].…”
Section: Dsc Analysismentioning
confidence: 98%
See 2 more Smart Citations
“…This phenomenon was evident due to the evolution of the material properties, namely, the concurrent increase in electrical conductivity and hardness. Furthermore, several previous investigations have shown that a high dislocation density significantly improves the kinetics of precipitation [5,[34][35][36] and recrystallization [33,37,38].…”
Section: Dsc Analysismentioning
confidence: 98%
“…All plots show straight lines, with high Pearson correlation coefficients of r 2 = 0.991 for the undeformed specimen and r 2 = 0.982 for the cold-rolled specimen. The activation energies were calculated from their slopes, and are listed in dislocation density significantly improves the kinetics of precipitation [5,[34][35][36] and recrystallization [33,37,38].…”
Section: Determination Of Precipitation Activation Energiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be attributed to the fact that cold rolling introduces various lattice defects such as dislocations and vacancies into the material, which provide additional nucleation sites for precipitation and thus lead to an accelerated reaction. Furthermore, several investigations have shown that a high dislocation density significantly improves the kinetics of precipitation [5,[34][35][36] and recrystallization [33,37,38].…”
Section: Dsc Analysismentioning
confidence: 99%
“…There are several hardening mechanisms for copper, which is very soft in its pure state [2], to obtain the desired properties. One of the most important hereby is precipitation hardening, which allows both, the otherwise conflicting mechanical strength of an alloy and the electrical conductivity to be increased by optimizing the microstructural properties during specific heat treatments [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%